Ethics in school : from moral development to children's conceptions of justice - Backman, Ylva; Haglund, Liza; Persson, Anders; Gardelli, Viktor (Luleå tekniska universitet, Pedagogik, språk och Ämnesdidaktik, 2009)
A main issue in Swedish school debate is the question of how to teach the student a common value system based on democracy and western humanism. The debate is rather intense, to say the least. Not only is the premise that there exists one value system that we share a target for critique, but there is also the question of what value education is or could be. There is, as well, quite a body of research on children's moral development, where many take as their departure the work of Kohlberg. However, there has been little or no attention on how the individual learner conceptualizes and makes meaning out of ethical issues. That is, descriptions of processes. In this paper we will present what we take to be urgent questions that need to be investigated against the background of prior research and practical work at Södra teatern in Stockholm, Sweden. For eight years in a row, Södra teatern has had as a main project to lead a practice on the subject of philosophy with children. Several groups of youths in the age of nine to eighteen have regularly met to discuss philosophical thoughts and problems, which in a democratic manner are settled for discussion by the participants. Today this philosophical practice has spread to the north of Sweden. In Backman's final exam within the teacher education she has explored the development of children's (7‐8 years old) ability to argue for different ethical positions, both verbally and in writing and painting. This practice has been inspired by the tradition at Södra teatern, but customized to fit a regular school class in Luleå, with very little experience of philosophical discussion. In the very short period of five weeks Backman has been able to see quite significant changes in the children's ability to argue for their ethical positions. The study was initiated by examining some argumentative abilities of the pupils, for instance the ability of expressing an argument for an ethical position in writing. In the final part of the study, the same ability was examined in very similar ...